2000
DOI: 10.1080/08897070009511415
|View full text |Cite
|
Sign up to set email alerts
|

Training Community‐Based Clinicians in Screening and Brief Intervention for Substance Abuse Problems: Translating Evidence into Practice

Abstract: Screening and brief intervention in general health care settings are efficacious but have not been widely adopted. Our objective was to assess the effect of an educational intervention on clinicians' substance abuse-related clinical practices. The study was a telephone survey of practicing physicians, nurses, psychologists, physician's assistants, and social workers who attended a half-day continuing education course on one of four occasions. The course covered the stages of behavioral change and motivational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 50 publications
1
44
0
2
Order By: Relevance
“…One additional study (Saitz, Sullivan, & Samet, 2000) reported a mix of health care workers, psychologists, and social workers. Table 1 shows a summary of the workshops that focused on health care providers.…”
Section: Resultsmentioning
confidence: 97%
“…One additional study (Saitz, Sullivan, & Samet, 2000) reported a mix of health care workers, psychologists, and social workers. Table 1 shows a summary of the workshops that focused on health care providers.…”
Section: Resultsmentioning
confidence: 97%
“…Several of the studies reported positive findings. Saitz et al [41] showed that training had a significant effect on practice as the participants screened and asked more patients about their substance abuse. Similarly, Sargeant et al [42] observed that participants made specific changes in their counselling approaches and felt more comfortable interacting with patients.…”
Section: Outcomes: Clinical Use Of MImentioning
confidence: 98%
“…Training in the form of continuing education for GPs and other health professionals in the wider community has been found to increase their willingness to offer alcohol screening and to ask patients about alcohol [18,20]. For these reasons, training was a key feature of this project.…”
Section: The Impact Of the Trainingmentioning
confidence: 98%